125k views
2 votes
How to work -1x-2y=-13 x-2y=11 equation by substitution

User TusharJ
by
7.7k points

1 Answer

0 votes
well if you're wanting to use substitution, you first have to end up with one term on either side of the equation. Use the second one as it's easiest.

So: x-2y=11, so find -2y as there is a -2y in the first equation.
then that becomes -2y=11-x. then sub that into equation 1, and you get:

-x+11-x=-13, which equals to -2x+11=-13, which is -2x=-24, so therefore

x=12. then chuck the x into any of the equations to find what y equals.

hope this helps!
User Mark Hill
by
7.6k points